Genre, migrations et sédentarités - Colette Le Petitcorps (EchoGéo)
After forty years dedicated to domestic service in France, a few Mauritian women come back to Mauritius in order to retire. We focus on their situation, space practices and social image in the place of their return home by bringing together an insight on their migration (hi)story and an analysis of the various ways by which migrations and settling processes patterns interact. The women narratives and the interviews with some people from their neighborhood in Mauritius gathered through fieldwork help understanding the sense of migration and of settled way of life from the subject point of view. Furthermore, this case study helps examining the gender norms that shape women migrations in domestic services.